Revisiting Winter Southern Ocean CO2 Uptake Based on CALIPSO Observations - Hao Huang; Ke Zhang; Zhaoru Zhang; Walker Smith Jr.; Jianfeng He; Na Liu; Chengfeng Le (Geophysical Research Letters)
Abstract The absorption of atmospheric carbon dioxide (CO2) in the Southern Ocean represents a critical component of the global oceanic carbon budget. Previous assessments of air‐sea carbon flux variations and long‐term trends in polar regions during winter have faced limitations due to scarce field data and the lack of ocean color satellite imagery, causing uncertainties in estimating CO2 flux estimation. This study utilized the Cloud‐Aerosol Lidar and Infrared Pathfinder Satellite Observation satellite to construct a continuous 16‐year (2006–2021) time series of sea surface partial pressure of CO2 (pCO2) in the Southern Ocean. Our findings revealed that the polar region in South Ocean acts as a carbon sink in winter, with CO2 flux of ∼30 TgC in high‐latitude areas (South of 50°S). This work highlights the efficacy of active remote sensing for monitoring sea surface pCO2 and contributes insights into the dynamic carbonate systems of the Southern Ocean.